2015
DOI: 10.1177/1359104515589640
|View full text |Cite
|
Sign up to set email alerts
|

The attachment of prematurely born children at school age: A pilot study

Abstract: This prospective longitudinal study compared the psychological development and patterns of attachment of 20 prematurely born children and 20 full-term children at 7 years of age. The School-age Assessment of Attachment (SAA) was used, and hypotheses and interpretation of the findings were drawn from the Dynamic-Maturational Model of Attachment and Adaptation (DMM). Significant differences between prematurely born and full-term children were found: 10% versus 0% at "high" risk, 55% versus 25% at "moderate" risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The distribution of SAA classifications can be seen in Table 1. In other studies, the SAA discriminated between clinical and normative status (Crittenden et al, 2010;Crittenden, Robson, & Tooby, 2015;Kozlowska & Elliott, 2015;Kwako, Noll, Putnam, & Trickett, 2010;Nuccini, Paterlini, Gargano, & Landini, 2015).…”
Section: Methodsmentioning
confidence: 84%
“…The distribution of SAA classifications can be seen in Table 1. In other studies, the SAA discriminated between clinical and normative status (Crittenden et al, 2010;Crittenden, Robson, & Tooby, 2015;Kozlowska & Elliott, 2015;Kwako, Noll, Putnam, & Trickett, 2010;Nuccini, Paterlini, Gargano, & Landini, 2015).…”
Section: Methodsmentioning
confidence: 84%
“…The finding regarding risk versus non-risk was replicated by Kwako, Noll, Putnam, and Trickett (2010) on an American sample; Crittenden, Robson, and Tooby (this issue) on a British sample; and Nuccini, Paterlini, Gargano, and Landini (this issue) on an Italian sample. Strikingly, the greatest differences were not in protective attachment strategy, but rather in depression and unresolved trauma.…”
Section: Validating the Saamentioning
confidence: 84%
“…They found that conversion disorders were heterogeneous with three types (A, C, and A/C), reflecting different neurobiological processes for coping with stress and requiring different forms of treatment. Nuccini and her colleagues explored the relation of very low birth weight to children’s attachment strategies (Nuccini et al, this issue). They found that low birth weight children used extreme self-protective strategies, particularly feigned helplessness.…”
Section: Validating the Saamentioning
confidence: 99%
“…Prematurity : Prematurely born children used risk protective attachment strategies, thus suggesting their interpersonal needs and adding to the validity of the SAA as a risk-sensitive assessment (Nuccini et al, 2015).…”
Section: B the Studies By Dmm Researchers Produced Many Clinically Rmentioning
confidence: 99%
“…Prematurity: Prematurely born children used risk protective attachment strategies, thus suggesting their interpersonal needs and adding to the validity of the SAA as a risk-sensitive assessment (Nuccini et al, 2015). Cultural context: Community and national contexts that contained danger adversely affected children's developmental experience.…”
Section: Special Risk Groupsmentioning
confidence: 99%